PENGARUH KOMPOSISI MORTAR KAPUR SEBAGAI PEREKAT SUSUNAN BATU CANDI SIWA PRAMBANAN TERHADAP KUAT GESER DAN INTERFACE - , BRIAN KRISNA YANRIZKY RINO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Prambanan Shiva temple is one of Indonesia precious historical relics and has been designated a World Heritage Site by UNESCO in 1991. The earthquake occurred on May 27 th , 2006 has caused severe and extensive damage to the structure of the rock. Required stone temples crack filler material which is able to improve the condition of rock strength. Filler material should be weaker than the strength of the stone temple so that in case of the temple structure failure, new damages are not formed. Also the first muffling and breaking dynamic load is filler material so obtained elasticity of the structure as seen from the shear strength parameters. Conducted a study to determine the filler made from a mixture of sand, lime, red cement, and water with some kind of mix, distribution of grain, water factors and certain ratios are expected to get a goodmix of filler in strength and workability. The research was conducted by direct shear tests and interface shear test with three types of stone temples